Nutrition for sport and exercise - Dunford, Marie; Doyle, J. Andrew; Killian, Lauren (Cengage, 2022)
"Dunford/Doyle's NUTRITION FOR SPORT AND EXERCISE, 5th Edition combines the best of theory and research-- emphasizing scientific reasoning and the latest studies around current nutritional recommendations. NUTRITION FOR SPORT AND EXERCISE illustrates the connections among exercise, nutrition and--the ultimate goals--optimal performance and health. Explaining the rationale behind the recommendations made to athletes, the authors help readers create specific plans for selecting the appropriate amount and type of foods, beverages and/or supplements to support training, performance and recovery. This text is available with MindTap, the platform that gives instructors a wealth of resources and content to help propel students from memorization to mastery."--Publisher's description.